So, about modern Europe... : a conversational history from the Enlightenment to the present day - Imhoof, David Michael, 1970- (London, England : Zed Books, 2021)
"Starting with the Enlightenment, Europeans developed big ideas that have increased opportunities for people around the world and raised standards of living. But those same ideas have also produced wars, genocide, colonialism, and the potential for global environmental disaster. In a natural, funny and engaging style, Imhoof guides us through the good, the bad and the indifferent of modern European history"--
(Re)birthing new ideas in the Renaissance -- Science is a human invention -- The Enlightenment will free you and mess you up -- Now, that's a revolution! (France, 1789) -- I've got a fever, and the only prescription is more Nationalism! -- Industrialization, or: welcome to the machine -- On the road again: the ideas and violence of Western Imperialism -- Look, we've got to talk about the Enlightenment -- World War I: the war that did nothing but changed everything -- Between the wars without a center, or: up the creek without a paddle -- Downhill all the way: World War II and the Holocaust -- The Cold War as a line in the sand -- The long, strange and not-so-complete death of Colonialism -- The end of history, or something like that -- You do you: identity politics.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: European history; Europe -- History -- 1492-; Electronic books